Enhancing the reliability of floating offshore wind turbine towers subjected to misaligned wind-wave loading using tuned mass damper inerters (TMDIs) - Fitzgerald, Breiffni (My University, 2023)
Floating offshore wind turbines (FOWTs) are the largest rotating structures on the earth. Dynamically sensitive structures such as these must be protected in these environments to ensure that they can continue to operate reliably and safely. In this paper structural dynamic models and probabilistic assessment tools are combined to demonstrate improvements in structural reliability when FOWT towers are equipped with a new type of damper — the tuned mass damper inerter (TMDI). A multi-body dynamic approach is used to model the wind turbine and the TMDI installed in the tower. The model is subjected to stochastically generated wind and wave loads of varying magnitudes to develop wind-induced probabilistic demand models for towers of FOWTs under model and load uncertainties. A focus is placed on the impact of the wind-wave misalignment on the lightly damped side-to-side mode. Numerical simulations are carried out to construct fragility curves which illustrate reductions in the vulnerability of FOWTs to wind and wave loading owing to the inclusion of the new damper. Results show that the TMDI delivers significant increases in structural reliability of FOWT towers.
PUBLISHED
Keywords: Tuned Mass Damper Inerter (TMDI); Stochastic wind-wave loads; Spar-type floating offshore wind turbine; Fragility analysis; Smart & Sustainable Planet; Structural Dynamics; Structural Engineering; Wind Energy and Wind Turbines; Wind, Wind Energy Engineering